How to understand the principle of non-splitting of shares in Polish and German company law - a tale of historical equivalence and comparative importance - Szczepańska, Katarzyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The article examines the understanding of the principle of non-split-ting, showcasing the historical and comparative equivalence of the German and Polish legal systems. It concerns the non-splitting of shares in Polish and German law, as applied to the limited liability company and the non-public joint-stock company. It is aimed at conceptualizing in a comparative manner the theoretical model of non-splitting, and encompasses discussions about its nature, content, and normative bases for its binding force. Under Polish law two different understandings of the principle of non-splitting of shares are distinguished: the principle of non-splitting in the strict sense, and the principle of non-splitting in the broad sense. It is argued that German law uses the concept of prohibition of splitting, while in the Polish legal system this concept has been further developed and is to be perceived as a principle of non-splitting of shares that is to be classified as general principle of company law.